2010
DOI: 10.1124/jpet.110.169433
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Renal Clearance of a Zwitterionic Substrate Cephalexin in Mate1-Deficient Mice

Abstract: Multidrug and toxin extrusion 1 (MATE1/solute carrier 47A1) mediates the transport of not only organic cations but also zwitterions such as cephalexin. However, the contribution of MATE1 to tubular secretion of cephalexin in vivo has not been elucidated. In the present study, we carried out transport experiments of cephalexin via MATE1 and performed pharmacokinetic analyses of cephalexin in Mate1 knockout [Mate1(Ϫ/Ϫ)] mice. Cephalexin uptake by human MATE1-expressing human embryonic kidney 293 cells exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…7). TEA, metformin, and cephalexin were selected as test drugs, the tubular secretion of which is mediated by Mate1 (Tsuda et al, 2009b;Ito et al, 2010;Watanabe et al, 2010). Cimetidine significantly reduced the renal clearance of TEA and cephalexin with regard to the plasma concentration, but not metformin, and it increased the kidney-to-plasma ratio of TEA, metformin, and cephalexin (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). TEA, metformin, and cephalexin were selected as test drugs, the tubular secretion of which is mediated by Mate1 (Tsuda et al, 2009b;Ito et al, 2010;Watanabe et al, 2010). Cimetidine significantly reduced the renal clearance of TEA and cephalexin with regard to the plasma concentration, but not metformin, and it increased the kidney-to-plasma ratio of TEA, metformin, and cephalexin (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Drug transporters play an indispensable role in the active tubular secretion of drugs in the proximal tubules. For cationic drugs, the basolateral uptake is mediated by OCTs (Oct1 and Oct2 in rodents and OCT2 in humans) and proton/organic cation exchangers, MATEs (Mate1 in rodents and MATE1 and MATE2-K in humans), which are considered to mediate the efflux of cationic drugs into the urine (International Transporter Consortium et al, 2010;Mate1 has markedly delayed the systemic elimination of metformin and cephalexin in mice, indicating the importance of Mate1 in the renal elimination of cationic drugs (Tsuda et al, 2009a;Watanabe et al, 2010). We also demonstrated that a potent MATE inhibitor, pyrimethamine, significantly reduced the luminal efflux of TEA and metformin in the liver and kidney in mice (Ito et al, 2010) and the renal clearance of metformin in healthy human subjects (Kusuhara et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…MATE1 and MATE2 proved to display the "physiological fingerprint" of the apical element of renal (and hepatic) OC secretion: 1) substantial expression in the luminal membrane of RPT cells (and, for MATE1, canilicular membrane of hepatocytes), 2) support of OC/H ϩ exchange, and 3) transport of structurally diverse OCs. The quantitative link between MATE activity and renal OC secretion was then firmly established by the observation that elimination of Mate1 in mice significantly reduces renal clearance of metformin (Tsuda et al, 2009) and cephalexin (Watanabe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A primary focus of studies of MATE function has been establishing the interaction of MATE transporters (typically MATE1) with specific structural classes of drugs (Yokoo et al, 2007;Ohta et al, 2009;Watanabe et al, 2010;Cutler et al, 2012). However, lacking in these observations is an effort to identify the molecular determinants of ligand (substrate/ inhibitor) interaction with MATE transporters, including establishing the differential selectivity of MATE1 versus MATE2 (Masuda et al, 2006;Komatsu et al, 2011) or with its kidney-specific isoform, MATE2-K.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the in vitro-determined K m values do not necessary preclude the kinetic impacts of the transporter in vivo. For instance, some drugs of high K m values determined in vitro play a significant role in MATE1 excretory pathways in vivo (42).…”
Section: Discussionmentioning
confidence: 99%